2018
DOI: 10.1007/s12187-018-9547-2
|View full text |Cite
|
Sign up to set email alerts
|

Parental Social Support and Adolescent Well-Being: a Cross-Sectional Study in China

Abstract: The aim of this study was to examine whether the two components of parental social support, emotional and instrumental, are associated with various aspects of adolescent well-being in the current Chinese context. A sample of 1306 adolescents (47% girls, 11, 13 and 15 years old, 39% urban) was derived from the nationally representative 2012 survey "China Family Panel Studies". Four indicators of adolescent well-being were examined: health status, academic attainment, self-perception and depression. Logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
4
14
0
Order By: Relevance
“…We also found that the relation between the quality of mother-adolescent relationships and adolescents’ well-being was significantly stronger than that between father-adolescent relationship quality and adolescents’ well-being. This finding suggests the importance of investigating the effects of both parents on adolescents’ well-being, supporting our expectations based on family systems theory (e.g., [ 30 ]) and previous research [ 23 , 60 , 61 ]. Adolescence is characterized by social transformations, among others [ 1 ], and research suggests that the relative roles of mothers and fathers change between adolescence and young adulthood [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that the relation between the quality of mother-adolescent relationships and adolescents’ well-being was significantly stronger than that between father-adolescent relationship quality and adolescents’ well-being. This finding suggests the importance of investigating the effects of both parents on adolescents’ well-being, supporting our expectations based on family systems theory (e.g., [ 30 ]) and previous research [ 23 , 60 , 61 ]. Adolescence is characterized by social transformations, among others [ 1 ], and research suggests that the relative roles of mothers and fathers change between adolescence and young adulthood [ 61 ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests the importance of investigating the effects of both parents on adolescents’ well-being, supporting our expectations based on family systems theory (e.g., [ 30 ]) and previous research [ 23 , 60 , 61 ]. Adolescence is characterized by social transformations, among others [ 1 ], and research suggests that the relative roles of mothers and fathers change between adolescence and young adulthood [ 61 ]. Thus, future research should investigate the unique roles of mothers and fathers with respect to adolescents’ internalizing problems and well-being over time.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Padilla-Walker et al. (2016) found that parental warmth was positively related to adolescents’ pro-social behaviors; low instrumental support was associated with lower self-perception and higher level of depression (Wang et al., 2018), and there are negative associations between perceived parental support and behaviors problems (Yun et al., 2016), such as alcohol use (Maslowsky et al., 2016). Similarly, an inverse relationship has been found between perceived familial support and cigarette smoking (Hamid et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that cultural capital, such as parental reading and family participation in cultural activities, is irrelevant or negatively related to East Asian adolescents’ academic achievements (Byun et al, 2012; Yamamoto & Brinton, 2010). Even parental support that is directly related to improving skills and knowledge for testing, such as educational supervision, has been found to have no association with Chinese adolescents’ academic performances (Wang et al, 2019). This result is consistent with the discussion of ‘education fever’ (Byun et al, 2012) in East Asian families—that is, parents being keen to involve themselves in their children’s educational careers (Liu & Xie, 2015).…”
Section: Parental Influence Relational Approach and Educationmentioning
confidence: 99%
“…Parents are a fundamental influence in the everyday lives of young people (Lahelma & Gordon, 2008; Milne & Aurini, 2015; Wyn et al, 2011). This is particularly true in China (Byun et al, 2012; Chao & Tseng, 2002; Wang et al, 2019), where parents’ high demands for their children’s education have been widely researched. However, rapid societal change has reshaped the traditional authoritarian parenting style in contemporary China.…”
Section: Introductionmentioning
confidence: 99%